Nutrition Adequacy Level of Pregnant Women and Toddlers Aged 0 to 24 Months in Gianyar Regency - Luh Gede Pradnyawati; Dewa Ayu Putu Ratna Juwita; Anak Agung Sagung Mirah Prabandari; Made Indra Wijaya (Warmadewa University, 2023)
Stunting has become a national issue that has received a lot of attention recently, as stunting can affect the nation's productivity in the future. The adequacy of nutritional intake in months 0 up to 24 months, or 1000 days of life, is one of the key factors in preventing stunting. This study aims to determine the nutrition adequacy level of pregnant women and children aged 0 to 24 months in Gianyar Regency. This study was a household survey with a cross-sectional approach. The samples were households in Gianyar Regency in 2021 with pregnant women and young children (up to 24 months old), chosen using the cluster method with the census block serving as a cluster. From each selected census block, 5 samples of pregnant women, 5 samples of children aged 0–1 year, and 5 toddlers aged 1-2 years will be selected by a simple random method. Data was collected using the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ). Data analysis was performed using the NutriSurvey application. The total energy of pregnant women was moderately deficient; protein and fat adequacy were normal, while carbohydrates, calcium, and iron were severely deficient. Nutritional adequacy for toddlers aged 0–1 year in the form of energy, protein, fat, carbohydrates, calcium, and iron was classified as normal. Nutritional adequacy for toddlers aged 1-2 years in the form of energy, protein, fat, calcium, and iron was classified as normal, while carbohydrates were moderately deficient. The presence of nutrition deficiencies among pregnant women indicates that a public health program regarding carbohydrate, calcium, and iron deficiencies is urgently needed.